PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR ASET DAN OPERATING LEVERAGE TERHADAP STRUKTUR MODAL - Lie, Grace Jocelline; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research will analyze the capital structues of property and real estate companies trading on the Indonesia Stock Exchange (IDX) from 2018 to 2021 in order to ascertain the impact of profitability, liquidity, asset structure, and operating leverage. These results are based on data collected from 2018–2021. A total of 41 properties and real estate firms were included in this study, which used 96 data points overall. The researchers in this study used SPSS 26 to analyze the data they collected using a sample selection strategy based on a purposive sampling strategy. The findings revealed a negative and statistically significant relationship between capital structure and profitability, liquidity, and the composition of assets. However, operating leverage does positively affect capital structure, albeit to a small degree. A company's capital structure is influenced by its profitability, liquidity, asset structure, and operating leverage all at once. This study has important implications for future company management, including how to select a highly profitable profitability to maximize the value of a company eager to broadcast positive signals to investors.